Criptografia RSA: a teoria dos números posta em prática - Souza, Lana Priscila (2015)
Since the advent of writing, sending secret messages has been an important way to maintain confidentiality of sensitive information. The art of crafting messages from secret codes appears in the figure of encryption that over time extends its services to commercial transactions over the Internet. The main algorithm used by the internet is called RSA. Thus, the RSA Encryption encodes credit card numbers, bank passwords, account numbers and uses for that elements of an important area of mathematics: number theory.